PLGA nanoparticles for intravitreal peptide delivery: statistical optimization, characterization and toxicity evaluation. (21st April 2018) - Bisht, Rohit; Rupenthal, Ilva D.
Abstract: Frequent intravitreal injections are currently used to overcome the ocular barriers and provide sufficient drug to the posterior eye segment. However, intravitreal injections have been associated with a number of complications and high treatment costs. To overcome these limitations, peptide-loaded poly(d, l -lactic- co -glycolic acid) nanoparticles (PLGA NPs) were developed using the nanoprecipitation technique and were optimized via Box–Behnken Design (BBD) and Response Surface Methodology (RSM). Developed NPs were evaluated for potential toxicity and cell apoptosis using the zebrafish embryo toxicity (ZET) model with titanium dioxide NPs and ethanol (1% v/v) serving as positive controls. Developed NPs had a size of 75.6–153.8 nm, a polydispersity index between 0.11 and 0.25 and a zeta potential of −9.4 to −46.0 mV. Loaded peptide was found to be stable under various experimental conditions tested. BBD and RSM were validated through the characterization of optimized formulations. Survival and hatching rates of NP-treated zebrafish 0–144 h post-fertilization were found to be normal with no significant malformations. Cellular apoptosis studies also endorsed the non-cytotoxic nature of the NPs. The overall results indicate that optimized PLGA nanoparticles could be a promising platform for efficient peptide delivery to the posterior segment of the eye.